A multi-agent system for web services discovery in a UDDI cloud. (1st December 2014) - Bouyakoub, Fayçal M'hamed; Belkhir, Abdelkader; Mellal, Mohamed Amine
Web services are playing an important role in several areas. However, with the proliferation of these services, the task of searching for relevant services becomes more and more difficult. This paper presents a new framework for web service publication and discovery in a distributed architecture. The framework, based on a multi-agent system, gives services' publishing and searching, another dimension. The service description includes an enriched representation, composed of contexts and quality of service (QoS) parameters, in order to make more efficient the discovery and selection stages. This representation (user/service contexts and QoS parameters) is taken into account during the discovery process. The search agent uses a new quantitative similarity measure to calculate the correspondence rate between the client and the services profiles in order to provide users with appropriate services according to their contexts and required QoS parameters.